PENGARUH JENIS PAKAN DAN KONDISICAHAYA TERHADAP PENAMPILAN WARNAIKAN PELANGI MERAH Glossolepis incisus JANTAN [Effect of Feeding Type and Light Intensity to The Color Appearance of Male Red Rainbow Fish, Glossolepis incisus] - Djamhuriyah S Said; W. D. Supyawati; nFN Noortiningsih (Jurnal Iktiologi Indonesia, 2005)
Glossolepis incisus is among the most beautiful members of the family Melanotaeniidae and the color of mature males is bright red, so it has the economical value as ornamental fish. The species is endemic at Lake Sentani - Irian. The problem found in rearing of the fish such as the decreasing of the color appearance and low growth rate. The research aimed to study the effect of feeding type and light intensity to the color appearance and growth rate of G. incisus (males). The research was conducted in September -December 2002 by utilizing three different feeds types, that were Chironomus, Tubificidae and pellet combination with light intensity (high: 300 lux and low 180 lux) in three replicates. Combination of pellet and light intensity (300 lux) is the best in color appearance, and Tubificidae treatment showed highest growth rate of the fish. Survival rate are 100%.